ANALISIS TERAPI SHALAWAT WABARIK TERHADAP SIKAP RELIGIUSITAS DAN KEJIWAAN SANTRI: Studi Kasus Santri Pondok Pesntren Al-Quran Nurul Arif Salam - Abdul Hobir; Subhan (Jurnal An-Nufus, 2025)
This research discusses the impact of the Shalawat Wabarik ritual on the psychological condition of the younger generation, in this case the santri at the Nurul Arif Salam Al-Quran Islamic Boarding School in Ciamis, West Java. This research method is qualitative with data collection through interviews, observation and documentation. The purpose of this research is to find out the extent to which the concept of Shalawat Wabarik is practiced among the students of the Nurul Arif Salam Al-Quran Islamic Boarding School in Ciamis on the psychological aspects of the students, including the supporting and inhibiting factors in its implementation and its relationship with the psychology of the students. The results showed that Shalawat Wabarik therapy at the Nurul Arif Salam Al-Quran Islamic Boarding School had a positive impact on the psychological condition of the students.